OPTIMALISASI STRATEGI POLMAS GUNA MENDUKUNG PENERAPAN PROTOKOL KESEHATAN SELAMA PANDEMI COVID-19 DALAM RANGKA TERWUJUDNYA SITUASI KAMTIBMAS YANG KONDUSIF - Alam, Kodrat; Dadan Kusumah, Asep (Yustitia, 2021)
Many people have not implemented health protocols in carrying out their daily activities is a special phenomenon that deserves serious attention from various parties, including elements of the Police in it. This is possible considering the implementation of the main functions and duties of the Police in the field of Kamtibmas which can reach up to the smallest units in society through the implementation of the Community Policing (Polmas) strategy. Polmas through adjustments to the implementation of the main functions and duties of Bhabinkamtibmas as Community Policing Bearers (Polmas) which are oriented towards achieving increased public awareness and compliance in implementing health protocols. In this concept, the researcher conducted research using normative juridical methods. This juridical approach is because this research analyzes existing legal aspects, and is normative because this research focuses more on the analysis of existing laws and regulations and other regulations, using secondary data, namely scientific references or other scientific writings as study material that can support the completeness of this scientific work Specifically regarding adjustments to the implementation of the main functions and duties of Bhabinkamtibmas as Community Policing Carriers (Polmas) which are oriented towards achieving increased public awareness and compliance in implementing health protocols, the implementation is carried out with the support and involvement of the Police and Community Partnership Forum (FKPM).